2019
DOI: 10.1039/c8sc04660c
|View full text |Cite
|
Sign up to set email alerts
|

A catalytic antioxidant for limiting amyloid-beta peptide aggregation and reactive oxygen species generation

Abstract: An Fe corrole is shown to bind to the amyloid-beta peptide and limit reactive oxygen species generation and peptide aggregation of relevance to Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 134 publications
4
40
0
Order By: Relevance
“…At each time point (3, 6, 11, and 24 h) a 30 µL aliquot was removed from the stock incubation solution for each treatment and kept at −80 • C until further analysis. An increase in high MW aggregates over time was observed for Aβ 1−42 alone (Lane 1, Figure 3), with a significant decrease in soluble Aβ species at 24 h, as expected based on prior results (Jones et al, 2015;Gomes et al, 2019). The Ru-N derivatives do not significantly affect aggregation at the 3 h timepoint.…”
Section: Influence Of Ru-n Series On Aβ Aggregationsupporting
confidence: 84%
“…At each time point (3, 6, 11, and 24 h) a 30 µL aliquot was removed from the stock incubation solution for each treatment and kept at −80 • C until further analysis. An increase in high MW aggregates over time was observed for Aβ 1−42 alone (Lane 1, Figure 3), with a significant decrease in soluble Aβ species at 24 h, as expected based on prior results (Jones et al, 2015;Gomes et al, 2019). The Ru-N derivatives do not significantly affect aggregation at the 3 h timepoint.…”
Section: Influence Of Ru-n Series On Aβ Aggregationsupporting
confidence: 84%
“…Previous studies have demonstrated that variations in cell toxicity are correlated with the Ab 40 aggregation state, meaning that they could be subject to potential modulation (i.e., enhanced or retarded toxicity) by porphyrinoid additives. [30][31][32] MMn appears particularly effective in this regard.…”
Section: Cellular Assays and Stability Studiesmentioning
confidence: 98%
“…The interaction of hemin and other water-soluble phthalocyanines, corroles, and porphyrins with Ab has been noted. [29][30][31][32] We thus envisaged that coupling the Ab-recognition properties of metalloporphyrins with the biological activity of metallotexaphyrins would allow for MRI recognition of Ab species with attendant utility as a potential metalloantioxidant therapeutic ( Figure 2). As detailed further below, we have found that metallotexaphyrins, in particular MMn, interact with amyloid constructs, as inferred from ultraviolet-visible (UV-vis), fluorescence, and circular dichroism (CD) spectroscopies, as well as MRI studies.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicated that the antioxidant defense system in some elderly people lost its ability to neutralize the oxidative substance. In the early AD stage, the oxidative stress could initiate the Aβ aggregation and tau protein hyperphosphorylation (Gomes et al, 2018). Many evidences have proved that the antioxidants could attenuate the AD syndrome, and prevent the disease progression (Gomes et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the early AD stage, the oxidative stress could initiate the Aβ aggregation and tau protein hyperphosphorylation (Gomes et al, 2018). Many evidences have proved that the antioxidants could attenuate the AD syndrome, and prevent the disease progression (Gomes et al, 2018). Thus, drugs with specifically antioxidant activity might be useful for either the prevention or the treatment of AD.…”
Section: Introductionmentioning
confidence: 99%